Lanthanum-based double perovskite oxides as cobalt-free catalyst for bifunctional application in electrocatalytic oxygen reactions - Singh D.P.; Mukherjee S.; Bhagat S.; Singh N.; Singh M.; Singh A.K.; Singh A.K.; Azad U.P.; Singh S.; Lalrintluangi; Singh V.P. (My University, 2025)
Electrochemical water splitting by use of suitable electrocatalysts is an important process to establish water as sustainable energy material. Similarly, the Oxygen reduction reaction is an important step involved in fuel cells. Hence, suitable catalysts are required for low-cost and high-performance activity towards both processes. In this work, we synthesized Cobalt-free Lanthanum-based double Perovskites oxides La0.5Sr0.5Fe0.8Cu0.2O3 and La0.5Sr0.5Fe0.8Zn0.2O3 by sol-gel method followed by calcination at different temperatures (800 °C, 900 °C and 1000 °C). Prepared double Perovskite oxide materials exhibit bifunctional catalytic activity towards both oxygen evolution reaction and oxygen reduction reaction. Calcination temperatures and composition have a significant impact on catalytic performance because of morphological control along with tuning of surface composition. Powder X-ray diffraction study has been performed to characterize the materials and phases/composition of materials was further analyzed by Rietveld refinement. The morphology of the best catalyst was analyzed by SEM, EDS mapping and XPS analysis. The catalytic performances of the catalysts were examined using electrochemical methods such as linear sweep voltammetry, cyclic voltammetry and electrochemical impedance spectroscopy in 0.1 M KOH solution. Preparation of noble-metal/cobalt-free catalysts is important finding towards establishing water as potential source for hydrogen production. © 2023 Hydrogen Energy Publications LLC